Fuzzy boundaries: Simulation and expertise in bushfire prediction. (December 2020) - Neale, Timothy; May, Daniel
It is becoming apparent that changes in climatic and demographic distributions are increasing the frequency and social impact of many 'natural hazards', including wildfires (or 'bushfires' in Australia). Across many national contexts, the governmental agencies legally responsible for 'managing' such hazards been called upon to provide greater foresight into the potential consequences, occurrence and behaviour of these dynamic phenomena. These conditions, of growing occurrence and expectation, have given rise to new anticipatory regimes, tools, practitioners and expertise tasked with revealing near and distant fiery futures. Drawing on interviews with Fire Behaviour Analysts from across the fire-prone continent of Australia, this article examines how their expertise has emerged and become institutionalized, exploring how its embedding in bushfire management agencies reveals cultural boundaries and tensions. This article provides important insight into the human and nonhuman infrastructures enrolled in predicting and managing landscape fires, foregrounding the wider social and political implications of these infrastructures and how their 'fuzzy boundaries' are negotiated by practitioners. Such empirical studies of expertise in practice are also, we suggest, necessary to the continued refinement of existing critiques of expertise as an individual capacity, derived from science and serving established social orders.